2014
DOI: 10.1001/jama.2014.14681
|View full text |Cite
|
Sign up to set email alerts
|

Nonobstructive Coronary Artery Disease and Risk of Myocardial Infarction

Abstract: IMPORTANCE Little is known about cardiac adverse events among patients with nonobstructive coronary artery disease (CAD). OBJECTIVE To compare myocardial infarction (MI) and mortality rates between patients with nonobstructive CAD, obstructive CAD, and no apparent CAD in a national cohort. DESIGN, SETTING, AND PARTICIPANTS Retrospective cohort study of all US veterans undergoing elective coronary angiography for CAD between October 2007 and September 2012 in the Veterans Affairs health care system. Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
285
1
10

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 473 publications
(333 citation statements)
references
References 42 publications
15
285
1
10
Order By: Relevance
“…Consequently, a standard protocol as used for MI‐CAD treatment may not apply uniformly to all MINOCA patients. These variations underscore the need for prospective pathophysiology‐driven studies that test primary and secondary treatments specific to MINOCA subtype 10, 54, 55, 56, 57…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, a standard protocol as used for MI‐CAD treatment may not apply uniformly to all MINOCA patients. These variations underscore the need for prospective pathophysiology‐driven studies that test primary and secondary treatments specific to MINOCA subtype 10, 54, 55, 56, 57…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence demonstrates that patients with MINOCA are distinct from patients with AMI with the classic culprit lesion—namely, >50% plaque‐mediated occlusion of the coronary artery (myocardial infarction due to coronary artery disease [MI‐CAD])—by having lower prevalence of the traditional cardiac risk factors and a lower but clinically significant annual mortality rate 1, 5, 6. Seen more commonly in women and young patients, existing literature on MINOCA is extrapolated from studies enrolling predominantly men and older patients, and this may limit opportunities to fully describe the different phenotypes of disease defined as MINOCA, their clinical profiles, and their associated outcomes 3, 6, 9, 10, 11…”
Section: Introductionmentioning
confidence: 99%
“…Patients with nonobstructive CAD are at increased risk of major adverse cardiovascular events, compared with those with no CAD 4, 7, 8. However, there is less guidance on the best treatment for patients with nonobstructive CAD.…”
mentioning
confidence: 99%
“…Several studies investigated the prognostic impact of the extent of anatomical nonobstructive disease evaluated by coronary angiography9, 20 or coronary computed tomography angiography 8, 21, 22. In the CONFIRM (coronary CT angiography evaluation for clinical outcomes: an international multicenter registry) registry,22 patients with 2‐ or 3‐vessel involvement of nonobstructive (1–49% diameter stenosis) CAD on coronary computed tomography angiography had a 3‐fold higher risk of all‐cause mortality than normal subjects.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of deferred lesions showed a gradual trend of decreasing event rates from the FFR strata of 0.76 to 0.80 to the strata of 0.81 to 0.85 8. Studies based on angiography and coronary computed tomography angiography showed that the extent of nonobstructive disease has prognostic implications (coronary artery disease [CAD]) 8, 9, 10. However, information about the influence of the extent of physiologically defined “moderate” CAD is limited.…”
mentioning
confidence: 99%